Textual Meaning in Song Lyrics - Edwan Ali Firdaus (Universitas Pendidikan Indonesia (UPI), 2013)
The study, entitled “Textual Meaning in Song Lyrics” is aimed to find out the most frequent Topical Theme in the song lyrics. The study used Systemic Functional Grammar to answer the research questions. The data were taken from dreamtheater.net involving three Dream Theater lyrics. Data were analyzed by Halliday Theme and Rheme analytical framework. The research shows that Topical Theme is the most frequent Theme which appears 70 times (68.63%) followed by Textual Theme which appears 28 times (27.45%) and Interpersonal Theme which appears 4 times (3.92%). The messages in the lyrics are mostly about love which is divided into three different points of view, i.e. the issue of love to an opposite sex, the issue of love to a son, the issue of love to life.Key-words: Theme, Topical, song lyrics, message.